Immune System Perspective in Intracerebral Hemorrhage Research: A Focus on Monocytes and Macrophages - Hang Hang; Lei Huang; Yuanhong Mao; Guofeng Wu (Brain Hemorrhages)
Monocytes and macrophages are crucial elements of the immune system, having various roles in tissue balance, inflammation, and conditions like stroke. They exhibit significant functional diversity, particularly evident in the M1 and M2 phenotypes and their marker characteristics. The functions of monocytes and macrophages are crucial in stroke studies, notably those related to intracerebral hemorrhage (ICH). ICH is the most severe type of stroke, characterized by inflammation, oxidative stress, and neuronal death, significantly increasing patient mortality and morbidity. Monocytes and macrophages play key roles in the inflammatory processes following ICH, participating in hematoma clearance and tissue repair. Despite their potential dual roles in the pathophysiology of ICH, involving both harmful and protective effects, the specific mechanisms remain to be further elucidated. This review summarizes the latest research progress on monocyte and macrophage subsets, with a particular focus on their contributions to ICH. It covers the relationships and differences between monocytes and macrophages, the functional diversity of macrophages, cell phenotypes and functions, regulatory mediators, gene expression and transcriptome analysis, and the clinical prognosis associated with blood monocyte counts. These research advancements aim to provide new insights for improving the diagnosis and treatment strategies for ICH.